2020
DOI: 10.1093/ejo/cjaa056
|View full text |Cite
|
Sign up to set email alerts
|

Influence of BMI percentile on craniofacial morphology and development in children and adolescents

Abstract: Summary Background The prevalence of childhood and adolescent obesity is increasing worldwide. Reports suggest that elevated body mass index (BMI) is associated with larger craniofacial dimensions and advanced dental and skeletal development. Such an association is important for timing orthodontic treatment relative to pubertal growth and dental eruption. Materials and Methods To evaluate ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…Genetic correlation was evaluated between the summary statistics of the NT-GWAS and anthropometric traits, blood lipids, hormones, and glycemic traits using the linkage disequilibrium (LD) score regression as implemented in the LD Hub database, making use of the already reported epidemiological association of these traits with dental maturation/eruption (Lal et al 2008; Partyka et al 2018; Danze et al 2021). We used only the NT GWAS summary statistics to avoid combining 2 proxies of dental maturation - NT and radiographic DD - in the LD Hub database (Zheng et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Genetic correlation was evaluated between the summary statistics of the NT-GWAS and anthropometric traits, blood lipids, hormones, and glycemic traits using the linkage disequilibrium (LD) score regression as implemented in the LD Hub database, making use of the already reported epidemiological association of these traits with dental maturation/eruption (Lal et al 2008; Partyka et al 2018; Danze et al 2021). We used only the NT GWAS summary statistics to avoid combining 2 proxies of dental maturation - NT and radiographic DD - in the LD Hub database (Zheng et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Overweight and obesity can alter bone metabolism, stimulate bone growth, inhibit bone remodeling, and increase the risk of musculoskeletal injuries (Dimitri 2019 ). Craniofacially, they can induce prognathism (Danze et al 2021 ), increased facial height (Cuccia et al 2007 ), early tooth eruption (Saloom et al 2017 ), and periodontitis (Zhu et al 2017 ). Growth hormone deficiency decreases growth velocity, leading to an immature facial appearance, short stature, hair deficiency, and delayed puberty (Ogilvy-Stuart and Shalet 1992 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study using geometric morphometric modeling of facial landmark data in 2D photographs 16 successfully predicted the BMI (32% of variance explained) and percentage body fat (21%). In addition to effects on soft tissue, recent studies have further clarified the influence of obesity or a high BMI on the hard-tissue craniofacial morphology using roentgen cephalograms 17 . These studies showed that obesity results in a greater facial size and bimaxillary protrusion with advanced maturation with or without vertical differences.…”
mentioning
confidence: 99%
“…These studies showed that obesity results in a greater facial size and bimaxillary protrusion with advanced maturation with or without vertical differences. This is assumed to be related to the fact that obesity can cause precocious puberty (earlier sexually development) and advanced bone maturity 17 , indicating the sexhormonal association of obesity.…”
mentioning
confidence: 99%
See 1 more Smart Citation